Knowledge and practices toward COVID-19 preventive measures and symptoms in general population: A case-control study in Benin - KEDOTE, Nonvignon Marius (My University, 2023)
Introduction. Following communication and awareness actions related to COVID-19, we assessed the knowledge and practices about COVID-19 in Benin. Methods. A case-control survey was conducted from 14 September to 20 October 2020 in Benin. Questions relating to knowledge and practices on COVID-19 were collected through a questionnaire survey. A total of 312 respondents (104 cases and 208 controls) were included in the study. Logistic regression and Spearman correlation tests were used to examine the relation between participants knowledge and practice at a 5% significance level. Results. From the survey, 65.4% of cases and 68.3% of controls knew about COVID-19 transmission via air droplets. Most of the cases (67.31%) and control (79.81%) participants reported cough as a symptom of COVID-19. Handwashing with soap and water was the most protective measure known by 87.5% of cases and 90.87% of controls. Concerning practice, the cloth mask was the type mostly worn by cases (54.81%) and controls (58.65%). Wearing a face mask in public areas was significantly associated with the COVID-19 health status of respondents (OR = 2.98, CI95% [1.16-7.67]; p = 0.022). Furthermore, a significantly positive correlation exists between knowledge of the COVID-19 protective measures and hand hygiene practices when leaving a public place (r = 0.184, p=0.001). Conclusion. Through this study, we observed some discrepancies between the knowledge and practices related to COVID-19 among cases and controls surveyed. Therefore, efforts should be directed toward raising awareness about the disease to improve their knowledge and practices.
Keywords: Benin; COVID-19; Case-Control; Knowledge; Practices